Mash-based analyses of Escherichia coli genomes reveal 14 distinct phylogroups - Kaleb Abram (Nature Portfolio, 2021)
Kaleb Abram and Zulema Udaondo et al. analyze over 100,000 publicly available E. coli and Shigella genome sequences and perform a Mash-based analysis to identify 14 unique phylogroups. Their results reveal that most of the sequenced E. coli genomes belong to four distinct phylogroups.